2014
DOI: 10.1007/s00426-014-0629-6
|View full text |Cite
|
Sign up to set email alerts
|

Reference frames in learning from maps and navigation

Abstract: In everyday life, navigators often consult a map before they navigate to a destination (e.g., a hotel, a room, etc.). However, not much is known about how humans gain spatial knowledge from seeing a map and direct navigation together. In the present experiments, participants learned a simple multiple corridor space either from a map only, only from walking through the virtual environment, first from the map and then from navigation, or first from navigation and then from the map. Afterwards, they conducted a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 27 publications
8
38
0
Order By: Relevance
“…This was consistently found after spatial learning that provided a fixed reference frame like cardinal directions of a map or environmental features (Brunyé, Burte, Houck, & Taylor, 2015;Frankenstein et al, 2012;McNamara, 2003;McNamara et al, 2003;Montello et al, 2004). After direct experience in the environment, which might lead to multiple local reference frames (Meilinger, 2008;Meilinger et al, 2015Meilinger et al, , 2006Montello et al, 2004) an alignment effect was much less consistently found (Burte & Hegarty, 2014;Presson & Hazelrigg, 1984). In agreement, our results revealed no alignment effect of tested house orientations towards north after direct experience in the virtual city.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This was consistently found after spatial learning that provided a fixed reference frame like cardinal directions of a map or environmental features (Brunyé, Burte, Houck, & Taylor, 2015;Frankenstein et al, 2012;McNamara, 2003;McNamara et al, 2003;Montello et al, 2004). After direct experience in the environment, which might lead to multiple local reference frames (Meilinger, 2008;Meilinger et al, 2015Meilinger et al, , 2006Montello et al, 2004) an alignment effect was much less consistently found (Burte & Hegarty, 2014;Presson & Hazelrigg, 1984). In agreement, our results revealed no alignment effect of tested house orientations towards north after direct experience in the virtual city.…”
Section: Discussionsupporting
confidence: 89%
“…In line with previous research (Meilinger, Frankenstein, Watanabe, Bülthoff, & Hölscher, 2015), we hypothesized to find a better task accuracy with smaller distances between tested houses (distance effect) with direct experience in Seahaven. As we have to be able to compare the distance between two houses for this analysis, we only considered the relative orientation and the pointing task.…”
Section: Accuracy As a Function Of Distancesupporting
confidence: 73%
See 2 more Smart Citations
“…Such a viewer-spacealignment experienced later during learning was found to be more important for determining reference frame orientation than initial views on a room (Kelly & McNamara, 2008;Shelton & McNamara, 2001;Valiquette & McNamara, 2007). A relatively simple environmental space (e.g., few orthogonally interlinked corridors) may still be represented along a single main axis that spans the entire environmental space (axis presumably aligned with the first vista space encountered; Meilinger, Frankenstein, Watanabe, Bülthoff, & Hölscher, 2015;Tlauka, Carter, Mahlberg, & Wilson, 2011;Wilson, Wilson, Griffiths, & Fox, 2007). However, sufficiently complex environmental spaces seem to be represented within multiple local reference frames, with each local corridor or street occupying a distinct reference frame aligned with the respective corridor (Meilinger et al, 2014;Werner & Schmidt, 1999).…”
Section: Reference Frame Orientationmentioning
confidence: 97%